BURNOUT SYNDROME IN SLOVAK TEACHERS IN RELATION TO SELECTED VARIABLES OF THE JOB DEMAND RESOURCES MODEL - Markovič, Daniel; Fričová, Júlia; Kohútová, Katarína (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The aim of this paper is to explore and analyse the prevalence of risk factors (and factors) associated with burnout among Slovak teachers. The research sample consists of 274 respondents: teachers, school principals, and other pedagogical staff. We used the Job Demand Resources Model (JD-R model), which suggests that the interplay between job demands and resources determines the overall impact on employee well-being. Jobs with high demands and low resources are likely to lead to burnout and health issues, while jobs with high demands but sufficient resources can lead to positive outcomes such as increased motivation and job satisfaction. Investigating burnout in teachers is essential for promoting the well-being of educators, maintaining a high-quality education system, and ensuring positive outcomes for both teachers and learners. Based on the Job Demand Resources Model, this study aims to analyse the relationship between selected variables and burnout syndrome among Slovak teachers.